Women and the gender of God - Peeler, Amy L. B. (Grand Rapids, MI, William B Eerdmans Publishing Company, 2022)
"A theological argument against the heresy that God is male and an affirmation of the truth that God values women, supported by a deep reading of the New Testament incarnation narratives and other relevant biblical texts"--
Includes bibliographical references (pages 225-250) and indexes.
Keywords: Masculinity of God; Women -- Biblical teaching; Femininity of God